Pengaruh Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian Produk Smartphone Iphone 11 di Kota Tangerang - Khoirunnisa, Fadilla Nur; Humairoh (BUDGETING : Journal of Business, Management and Accounting, 2025)
This study aims to determine the effect of product quality and price perception on purchasing decisions for iPhone  11 smartphones in Tangerang City. This study uses a quantitative approach with a population of residents in Tangerang City limited to the age of 15 - 49 years. The sampling technique used is non-probability sampling with a purposive sampling approach. The sample used was 100 respondents. The data analysis tool used was SPSS version 26. The results of this study indicate that partially, the variables of product quality and price perception have a positive and significant effect on purchasing decisions. Simultaneously, product quality and price perception have a positive and significant effect on purchasing decisions. The results of the determination test of 0.927 or 92.7% indicate that the variables of product quality and price perception affect purchasing decisions by 92.7%, and the remaining 7.3% are influenced by other variables not examined in this study. The novelty of this study lies in the different research objects. In contrast, previous researchers studied together that the variables of product quality and price perception are important factors that can shape purchasing decisions.     Keywords: Price Perception, Product Quality, Purchase Decision